Parents with intellectual disabilities : past, present and futures - Llewellyn, Gwynnyth (Malden, MA : Wiley-Blackwell, 2010)
Parents with Intellectnal Disabilities is a thoughful and comprehensive collection by an international team that blazes new trails for inclusion and equality for adults with intellectual disabilites. By asserting that forming a family and parenting are pathways both to social value and personal fulfilment, it challenges us to question our own values and assumptions about adults with intellectual disabilities as parents. An essential text for a full understanding of disability in the world of today and tomorrow Ivan Brown, Ph. D., Centre of Excellence for Child Welfare University of Toronto, Canada.
This is the first international, cross-disciplinary book to explore and understand the lives of parents with intellectual disabilities, their children and the systems and services they enocunter Contributors champion the rights of parents with intellectual disabilities, adovcating their full participation in the society and culture in which they live, in spite of stigmatizing attitudes and exclusionary practices.
This authoritative book examines the very latest research and scholarship on the subject Throughout the text, theory and research are linked to practice. The contributors provide a clear set of principles outlining how to work with parents with intellectual disabilities in ways that recognize family strengths and promote child and family well-being. Chapters are written by experts currently engaged either in academic study of the topic or as researcher-paracitioners in the field of intellectual disabilities. Each one provides a brief overview of the development of ideas and literature pertiment to the chapter's topic and concludes with principles drawn from the research to inform practice.
Written to reflect the United Nations Conention on the Rights of Persons with Disabilities (United Nations, 2006), the book provides a crucial reference for students, practtioners and prefessionals engagd in this area. --Book Jacket.
Introduction / g Looking Back on Their Own Upbringing / Gwynnyth Llewellyn and David McConnell -- Family Within a Family / t Part II: Human Services Enabling and Disabling Parents with Intellectual Disabilities -- Parenting Education Programs / Maurice Feldman -- Supported Decision Making for Women with Intellectual Disabilities / Sue McGaw and Sue Candy -- Turning Policy Into Practice / Beth Tarleton -- Caught in the Child Protection Net / t Marjorie Aunos, Laura Pacheco and Katherine Moxness -- Supporting Mothers' Community Participation / David McConnell and Gwynnyth Llewellyn -- Advocacy for Change: "The Final Tool in the Toolbox?" / Linda Ward and Beth Tarleton -- You have free access to this content -- Conclusion: Taking Stock and Looking to the Future.
Print version record.
John Wiley and Sons
Keywords: Parents with mental disabilities -- Cross-cultural studies; Parenting -- Cross-cultural studies; v; v; Parenting; Parents with mental disabilities; Geestelijk gehandicapten; Gezin; Ouder-kind-relaties.; Electronic resource; Cross-cultural studies